Laboratory preparedness and response with a focus on arboviruses in Europe. (March 2018) - Reusken, C.B.; Ieven, M.; Sigfrid, L.; Eckerle, I.; Koopmans, M.
Abstract: Background: The global health burden of arboviruses is continuously rising, which results in increasing pressure on local and (inter)national laboratory infrastructures. Timely and accurate diagnosis of cases is one of the main pillars for public health and clinical responses to an arbovirus emergence. Aims and sources: This narrative review aims to summarize recent advances and to identify needs in laboratory preparedness and response activities, with a focus on viruses transmitted by arthropods in Europe. The review is based on evidence extracted from PubMed searches, Public Health and clinical laboratory experiences from the authors and the authors' opinions substantiated by peer-reviewed scientific literature. Content: We illustrate the importance of inter-epidemic laboratory preparedness activities to ensure adequate Public Health and clinical responses. We describe the status of arbovirus endemicity and emergence in Europe thereby highlighting the need for preparedness for these viruses. We discuss the components and pitfalls of an adequate laboratory preparedness and response and the broader context of the current landscape of international research, clinical and laboratory preparedness networks. The complexity of arbovirus laboratory preparedness and response is described. Implications: Outbreak preparedness plans need to look beyond national reference laboratories, to include first-line responding onsite hospital laboratories and plans for strengthening of such local capacity and capability as required depending on the nature of the outbreak. In particular, the diagnosis of arbovirus infections is complicated by the existence of geographic overlap of circulation of numerous arboviruses, the overlap in clinical manifestation between many arboviruses and other aetiologies and the existence of cross-reactivity between related arboviruses in serology testing. Inter-epidemic preparedness activities need strong national and international networks addressing these issues. However, the current mushrooming of European preparedness networks requires governance to bring the European preparedness and response to a next level.